A intertextualidade na obra Libertinagem, de Manuel Bandeira: uma contribuição para o ensino de língua portuguesa - Abud, Mylene (2010)
In this essay, we investigate the importance of the intertextuality to establish new and different ways of reading. As our corpus, we elected some poems from the book Libertinagem, by Manuel Bandeira, which belongs to the author s modernist stage. Relation between one text and another or among others, all of them pre-existent, the intertextuality is one of the seven standards of textuality proposed by Beaugrande and Dressler. Seeing here in the field of Textual Linguistics, in lato or strict approach, in agreement or disagreement, the intertextual relations depend on the author/reader interaction, in order to ensure de coherence of the work and a higher degree of informativity. They also depends on the previous knowledge from de reader/receptor to reach the goals. Intertextuality enrichs the reading process and can be used as an importante tool in the classroom by mother tongue s teachers. This resource helps to develop a provocative, deep, funny and, most of all, critical reading